Antioxidant and antimicrobial activities of aqueous extracts of selected fruit peels and development of mixed fruit peel leather / Khairusy Syakirah Zulkifli - Zulkifli, Khairusy Syakirah (2014)
The discarding of fruit residues gain public’s attention as they might cause serious environmental pollution. Hence, a study was conducted on four different fruit peels namely Mangifera indica var. Chok-Anan, Psidium guajava var. Kampuchea, Citrus sinensis var. Navel and Malus sylvestris var. Granny Smith. For the first phase, fresh and dried aqueous extracts were screened for their phytochemicals and toxicity level, estimating the total phenolic content and total flavonoid content as well as quantification of individual phenolic. Antioxidant activity was conducted by using Ferric Reducing Antioxidant Power, DPPH Radical Scavenging, fi-carotene Bleaching and Oxygen Radical Absorbance Capacity while antimicrobial activity was evaluated against 10 bacterial and two fungal strains. The second phase comprised of development and optimisation of mixed fruit peel leather with formulations generated by Mixture Design. The results showed that C. sinensis exhibited the highest pectin yield and degree of esterification with 7.15% and 78.27%. All fruit peels extracts were classified as non-toxic with LC50 higher than 0.1 mg/ml. Fresh extracts were higher in TPC, TFC and both antioxidant and antimicrobial assays with M indica peel as the strongest confributor. M. sylvestris and M. indica also showed highest in total fiavonoid compound and total phenolic acids compound respectively that quantified by HPLC. A strong correlation was found between TPC with all antioxidant assays with r2 ranged from 0.732 to 0.989. The optimised formulation of mixed fruit peel leather by using sensory scores and TPC as responses was 56.50% P. guajava, 33.00% M. indica and 10.50% C. sinensis peels with desirability of 98.10. The optimised formulation also showed highest in TPC and all antioxidant assays. The development of mixed fruit peel leather is recommended as an alternative way to valorise fruit by-products.